FAKTOR-FAKTOR YANG MEMPENGARUHI PENDETEKSIAN FRAUD DENGAN KUALITAS AUDITOR INTERNAL SEBAGAI VARIABEL MODERASI - Ilma Maisarah (2022)
The study is quantitative research aims to examine the influence of internal audit effectiveness, internal control effectiveness, and continuance professional commitment to fraud detection with internal auditor quality as moderating. The population of this study are internal auditors and supervisors at the Inspectorate of South Tangerang City. The sample consisted of 43 respondents and selected by purposive sampling method. The analysis in this study is structural equation modeling (SEM) with the help of the SmartPLS version 3.0 program. The results of the study concluded that internal audit effectiveness and internal control effectiveness have a significant effect on fraud detection. Continuance professional commitment does not significantly affect fraud detection. internal auditor quality does not moderate the effect of internal audit effectiveness, internal control effectiveness, and continuance professional commitment to fraud detection.